2016
DOI: 10.2147/dddt.s93559
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of β-asarone against Alzheimer’s disease: regulation of synaptic plasticity by increased expression of SYP and GluR1

Abstract: Aimβ-asarone, an active component of Acori graminei rhizome, has been reported to have neuroprotective effects in Alzheimer’s disease. As the underlying mechanism is not known, we investigated the neuroprotective effects of β-asarone in an APP/PS1 double transgenic mouse model and in NG108 cells.Materials and methodsAPPswe/PS1dE9 double transgenic male mice were randomly assigned to a model group, β-asarone treatment groups (21.2, 42.4, or 84.8 mg/kg/d), or donepezil treatment group (2 mg/kg/d). Donepezil trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 35 publications
(27 reference statements)
0
49
0
Order By: Relevance
“…β-asarone is an ether found, e.g., in Acori graminei ( Liu et al, 2016 ). β-asarone treatment decreases Aβ42 levels in hippocampus and improves memory in a mouse model of AD, probably through mTOR-dependent autophagy ( Deng et al, 2016 ).…”
Section: Therapeutic Implications Of the Interplay Of Alzheimer’s Dismentioning
confidence: 99%
“…β-asarone is an ether found, e.g., in Acori graminei ( Liu et al, 2016 ). β-asarone treatment decreases Aβ42 levels in hippocampus and improves memory in a mouse model of AD, probably through mTOR-dependent autophagy ( Deng et al, 2016 ).…”
Section: Therapeutic Implications Of the Interplay Of Alzheimer’s Dismentioning
confidence: 99%
“…In the clinical context, β‐asarone exhibits various medicinal properties, such as anticancer (Liu et al, ; Wu et al, ; Zou et al, ), anti‐inflammatory, neuroprotective (Muthuraman & Singh, ), antiepileptic (Fu, Fang, Fang, Xie, & Fang, ), and antioxidant (Chaubey, Parki, Prakash, Kumar, & Pan, ) activities. β‐Asarone increased the expression of synaptophysin and glutamatergic receptor 1, deficiencies of which are associated with Alzheimer's disease, in APP/PS1 mice (Liu et al, ), and a 100‐mg/kg daily dose of β‐asarone improved learning and memory in a rat model of Alzheimer's disease because of galactose and aluminium chloride (Querfurth & LaFerla, ; Yan, Chen, Yan, Guo, & Chen, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, it was found that Bdnf and Gdnf gene expression was notably inhibited in HT22 cells cultured with HG, while fisetin pretreatment dramatically upregulated Bdnf and Gdnf expression, even higher than control group. Besides, it is widely believed that SYP can mediate synaptic structure and play a part in synaptic plasticity through phosphorylation and release of neurotransmitters (Liu et al, 2016). Chronic fluoride exposures reduced SYP expression and induced aberrant changes of GSK-3β/β-catenin signaling, leading to neuronal apoptosis and impaired synaptic plasticity (Jiang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%